IMPACT OF COSMIC RADIATION ON AVIATION RELIABILITY AND SAFETY - Zaczyk, Ian (Journal of Applied Engineering Science, 2013)
The main objective of this paper is to argue that the scientific approach to reliability and safety is the only way forward for the reliability community if accurate predictions regarding occurrences of negative functionability events are to be made and subsequently verified during the operational processes of the future man made, managed and maintained systems. For that to happen, a scientific understanding of the mechanisms that cause occurrences of functionability events of the surrounding natural environment are required. Then and only then, can accurate and meaningful reliability and safety predictions become possible, enabling the ultimate goal of reducing the probability of failure event occurrences during the life of man made, managed and maintained systems. This paper focuses on the scientific understandings of the relevant cosmic radiation on aviation reliability and safety.